Evaluation of Barley Genotypes (Hordeum vulgar l.) by drought tolerance indices and Multivariate analysis (Journal of Bio-Science, 2015)
Context: Evaluation of tolerance of different barley genotypes to drought stress, an experiment carried out in randomized block design (RCBD) with three replication during 2009-2010 growing seasons and 20 barley genotypes were studied in normal and water deficit in post anthesis stage conditions at the Saatloo Research Farm Azerbaiejan, Iran. Results: The result of variance analysis showed that there were highly significant differences between genotypes in all of the studied traits, also it was cleared that all of traits except spike length reduced in water deficit condition as compared to normal condition and seed yield, biomass and 1000 seed weight traits had the most reduction (31, 25 and 20 percent, respectively). To identify of tolerance barley genotypes to drought stress, drought tolerance indices (STI, TOL, SSI, MP, HM and GMP), correlation coefficients, principal components analysis and cluster analysis were used. The result of correlation coefficients indicated that there were significant and positive correlation between seed yield in normal and stress conditions and drought tolerance indices. Also the result of principal components analysis showed that two components justified 99% of total variations. MP, GMP, STI and HM indices and TOL and SSI indices had the most coefficients in the first and second component, respectively, so are named tolerance and sensitivity component, respectively. Conclusion: MP, HM, STI and GMP indices were appropriate indices to select of drought tolerance barley genotypes. On the other hand, the result of cluster analysis showed that 13, 14 and 7 genotypes and 18, 1 and 2 genotypes were tolerance and sensitivity genotypes to water deficit at post anthesis stage. DOI: http://dx.doi.org/10.3329/jbs.v21i0.22525 J. bio-sci. 21: 109-122, 2013